2012
DOI: 10.1371/journal.pone.0051855
|View full text |Cite
|
Sign up to set email alerts
|

Effective Inhibition of Human Immunodeficiency Virus 1 Replication by Engineered RNase P Ribozyme

Abstract: Using an in vitro selection procedure, we have previously isolated RNase P ribozyme variants that efficiently cleave an mRNA sequence in vitro. In this study, a variant was used to target the HIV RNA sequence in the tat region. The variant cleaved the tat RNA sequence in vitro about 20 times more efficiently than the wild type ribozyme. Our results provide the first direct evidence that combined mutations at nucleotide 83 and 340 of RNase P catalytic RNA from Escherichia coli (G83 -> U83 and G340 -> A340) incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The DNA sequences coding for V718-A, M1-A, V718-C, and M1-C were subcloned into retroviral vector LXSN which was used to express M1GS RNAs successfully in previous studies [ 8 , 33 , 40 ]. The constructed LXSN-M1GS vector DNAs were transfected into PA317 cells to produce vector particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA sequences coding for V718-A, M1-A, V718-C, and M1-C were subcloned into retroviral vector LXSN which was used to express M1GS RNAs successfully in previous studies [ 8 , 33 , 40 ]. The constructed LXSN-M1GS vector DNAs were transfected into PA317 cells to produce vector particles.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies on improving the cleavage efficacy of M1GS RNAs are important to develop ribozyme-based approaches [ 23 , 39 , 42 ]. However, no guidelines are currently available about how to generate a highly active M1GS RNA [ 23 , 39 , 40 ]. In this study, functional ribozymes (e.g., V718-A) were designed to target an accessible region of the overlapping region of AP and PR mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…1d ). A modifi cation to this approach has also been used to express bacterial RNase P (bRN-P) linked to an EGS to cleave a target in HIV-1 RNA [ 32 ]. The potential for using Group II intron Rzs for targeted intron insertion into HIV-1 DNA has also been explored [ 33 , 34 ], and future studies may identify new approaches to harness the activity of natural Rz motifs to inhibit HIV-1 replication.…”
Section: Design Of Anti-hiv-1 Ribozymesmentioning
confidence: 99%
“…Advantages of the U6 and H1 promoters for the expression of anti-HIV-1 RNAs include their precise transcription start and end sites, high transcriptional activity in different cell types and small size [ 72 ]. U6 or H1 promoters have been used to express HDV Rzs [ 28 ], RNase P-EGS Rzs [ 32 ] and several HH and Hp Rzs with different RNA conjugates added to enhance their inhibition of HIV-1 expression or replication (Table 1 ).…”
Section: Ribozyme Expression Strategiesmentioning
confidence: 99%
“…The first study on the use of EGSs targeting HIV demonstrated that EGSs targeting tat mRNA and long terminal repeat (LTR) RNA can successfully inhibit HIV replication in COS cells [ 59 ]. Later, Liu and coworkers developed an M1GS-based approach against HIV1, one of the two major types of HIV, by targeting the HIV tat mRNA [ 60 ]. An M1GS variant, with two mutations (G83U and G340A) led to 90% reduction of viral RNA expression and a 150-fold reduction in viral growth.…”
Section: Examples Of Rnase P-based Rna Knockdownmentioning
confidence: 99%